Walor prawny małżeństw tajnych w epoce kanonistyki klasycznej - Dzierżon, Ginter (Ius Matrimoniale, 2017)
By analysing source materials and present canonistic thought the author of the presented article proved that in medieval times secret marriages were legal. Disregarding legal formalities did not result in the invalidity of a legal act contracted by the nupturients. Although legal formalities were components introduced to the legal structure of marriage, they were not necessary in order for the marriage to be valid. Fulfilling the formal conditions was important only for evidential purposes. Moreover, the author proved that secret marriages in current codification (Cann. 1130-1133 CIC) work significantly different from how they functioned in the Middle Ages. In present times, the essence of this institution entails keeping secret specific stages of contracting marriage; in the times of Classical Canon Law, on the other hand, the aim was to contract marriage without fulfilling legal formalities.